Étude de la cluse fortifiée de Joux : le cas du bourg castral de Jougne - Valentin Metral (Bulletin du Centre d’Études Médiévales d’Auxerre)
The castral small town of Jougne has been involved since the Middle Ages in the control and defense of an ancient route crossing the Jura mountains. The case study carried out on the fortified works of Jougne using archive sources and the analysis of the preserved constructions revealed seven successive phases of construction, which offer a finer understanding of these evolving fortifications, showing reconstructions, modernizations and continuous maintenance of the place from the Central Middle Ages until the end of the modern era. Jougne remains indeed one of the few examples of the use of a small town in the defense of the French national territory in the 18th century. The study also makes it possible to better perceive the development of a castral mountain village with high archaeological potential and the importance of the latter in the history of the Comté region during five to six centuries. It requires further examination, extended to the network and fortified system of this crucial route and its area : the « Cluse de Jougne » also known as « Cluse du Fort de Joux », a fort that remains to be studied.